Arañas (Arachnida: Araneae) asociadas a dos bosques degradados del Chaco húmedo en Corrientes, Argentina - Ávalos, Gilberto (2007)
The advancing degradation of the forest in the biogeographic Chaco province (Argentina) produces an important loss of its little known biodiversity. We studied the spider biodiversity in two forests of Corrientes, Argentina’s “Distrito Oriental Húmedo del Chaco”: Laguna Brava and El Perichón. Seasonal samplings of foliage and fallen leaves between 2001 and 2002 produced 2 067 individuals from 33 families and 226 species/ morphospecies). The families Araneidae, Anyphaenidae, Salticidae and Theridiidae were the most abundant in both forests. The “orb weavers” guild had the highest number of specimens (n=382) and “stalkers” the highest richness (S=56). in Brava, highest abundance was in the summer (n=287) and spring (n=273), in Perichón, it was in winter (n=315). The specific richness and the diversity indexes were higher in Brava (S=134, H ́=4.23, E=0.86, D=0.023) than in Perichón (S=127, H ́=4.08, E=0.84, D=0.029). The similarity value between both forests was MH=0.611.